DOMIKADO GAME METHOD AS A MEDIA FOR BRUSHING TEETH’S EDUCATION FOR STUDENTS OF 02 TANGGULANGIN STATE ELEMENTARY SCHOOL - Latifah, Rose Asni; Setyawati, Erna; Sadimin, Sadimin (Journal of Applied Health Management and Technology, 2024)
Dental and oral health problems based on RISKESDAS 2018 data were recorded at 57.6%. In Wonogiri, the most common dental and oral health problem is regarding the lack of knowledge of brushing teeth. Efforts to improve knowledge of brushing teeth through education activities with the Domikado game method. This study aims to determine the Domikado Game Method as a education’s media to increase Toothbrushing Knowledge Improvement in 02 Tanggulangin Elementary School Students.This type of research uses quantitative descriptive with a pre-experimental research method and the research design used is one group pre-test post-test design. The sample in this study was taken using a saturated sample technique totaling 54 styudents. Knowledge measurement was carried out using pre-test and post-test questionnaires. Data analysis used quantitative descriptive analysis.The results of the study showed an increase in knowledge of brushing teeth which was originally in the moderate category of 41 (76%) students to a good category of 43 (80%) students. The conclusion of this study is that eduaction using the domikado game tends to be effective in increasing knowledge about brushing teeth because the domikado game is very interesting for elementary school students, most of whom are very enthusiastic about the game, trains students' concentration and the game is very exciting to play.